THE ROLE OF TEACHING PHONETICS IN LINGUACULTUROLOGY: CONNECTING SOUND SYSTEMS TO CULTURAL IDENTITY - Ruziyeva G. KH. (Bright Mind Publishing, 2025)
Phonetics, the study of speech sounds, plays a central role in language teaching by helping learners master pronunciation and enhancing communication. However, its contribution to linguaculturology—the study of the intersection between language and culture—is often overlooked. This paper examines the role of teaching phonetics in linguaculturology, focusing on how phonetic features reflect cultural values, social norms, and emotional expressions. By analyzing phonetic phenomena in both English and Uzbek, the study shows how phonetic patterns such as intonation, stress, and rhythm convey cultural meanings beyond mere linguistic accuracy. Using examples from traditional fairy tales, proverbs, and conversational data, the paper demonstrates that phonetics is not only a tool for linguistic competence but also a crucial element in understanding and teaching cultural identity through language. The findings underscore the importance of integrating phonetics in language education to promote both linguistic proficiency and intercultural competence.
Keywords: Phonetics; Linguaculturology; Language teaching; Cultural identity; Intonation; Stress patterns; Emotional expression; Cross-cultural communication.